1996
DOI: 10.1111/j.1745-4549.1996.tb00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Thermal Conductivity and Diffusivity of Soybean

Abstract: Bulk thermal conductivity of soybean, determined by the transient heat flow method, exhibited positive linear correlation with moisture content. The bulk thermal conductivity values increased from 0.1157 to 0.1756 W/m‐K in the moisture range of 8.1 to 25% d.b. Further, thermal diffusivity of soybean, computed from the values of thermal conductivity, specific heat and bulk density showed linear increase from 2.94 × 10−4 to 3.07 × 10−4 m2/h in the specified range of 8.1 to 25% d.b. moisture content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
4
18
0
1
Order By: Relevance
“…The linear and positive behavior of thermal diffusivity as a function of moisture content was similar to that reported by Deshpande and Bal (). These authors found for soybeans, values of thermal diffusivity in the range between 8.17 × 10 −8 and 8.53 × 10 −8 m 2 /s.…”
Section: Resultssupporting
confidence: 89%
“…The linear and positive behavior of thermal diffusivity as a function of moisture content was similar to that reported by Deshpande and Bal (). These authors found for soybeans, values of thermal diffusivity in the range between 8.17 × 10 −8 and 8.53 × 10 −8 m 2 /s.…”
Section: Resultssupporting
confidence: 89%
“…Bulk density of soybeans was assumed as constant and temperature independent during the simulated process. The bulk thermal conductivity and heat capacity values of soybeans were measured and reported by Deshpande, Bal, and Ojha (1996) and Deshpande and Bal (1999). Dielectric properties of soybeans at its particle density and 27 MHz were obtained from Guo et al (2010) in the range of 20-80°C.…”
Section: Physical Properties Of Samplesmentioning
confidence: 99%
“…5b) of soybeans, which increased with increasing temperature at moisture contents of 4.64 and 7.86% w.b. (Deshpande & Bal, 1999;Deshpande et al, 1996). These data were subjected to linear regression analysis (R 2 N 0.99) at temperature range of 20-80°C for using these properties in the simulation model.…”
Section: Model Parametersmentioning
confidence: 99%
“…The bulk density of dry soybeans at room temperature was measured by a basic volume method using a 30 Â 22 Â 6 cm 3 plastic rectangular container and obtained to be 739 ± 3 kg/m 3 over three replicates. Thermal properties (thermal conductivity and specific heat) at a bulk density of 739 kg/m 3 were calculated by Deshpande's regression equations [33,34]. Thermal properties of the insect larvae were reported by Ben-Lalli et al and Sahin and Sumnu with different measured components [32,35].…”
Section: Materials Properties Measurementmentioning
confidence: 99%